Reassignment of consonant allophones in rapid dialect acquisition - German, James S. (2014)
In an experiment spanning a week, American English speakers imitated a Glaswegian (Scottish) English speaker. The target sounds were allophones of /t/ and /r/, as the Glaswegian speaker aspirated word-medial /t/ but pronounced /r/ as a flap initially and medially. This experiment therefore explored (a) whether speakers could learn to reassign a sound they already produce (flap) to a different phoneme, and (b) whether they could learn to reliably produce aspirated /t/ in an unusual phonological context. Speakers appeared to learn systematically, as they could generalize to words which they had never heard the Glaswegian speaker pronounce. The pattern for /t/ was adopted and generalized with high overall reliability (96%). For flap, there was a mix of categorical learning, with the allophone simply switching to a different use, and parametric approximations of the “new” sound. The positional context was clearly important, as flaps were produced less successfully when word-initial. And although there was variability in success rates, all speakers learned to produce a flap for /r/ at least some of the time and retained this learning over a week's time. These effects are most easily explained in a hybrid of neo-generative and exemplar models of speech perception and production.